(untitled) (International Journal of Engineering and Computer Science, 2018)
TPO(Training And Placement Office) is required in every college for placement of students as well as exstudents. In existing system, all processes are handled manually. Students create and submit their CVs early in the year. TPO has to see each and every student marks and their eligibility. If anyone wants to talk with the TPO he has to go in a TPO cabin and take relevant information. The proposed Online Training and Placement application meant to give more easiness to the users that they can add and retrieve information so quickly. There are two types of student: Current Student and Alumni Student. Current Students can review and enter information around the clock and from any location. For alumni the last three years data will be maintained. Students on placement will also use the system to read important announcements, to obtain information on assessment, to see the results of assessments recorded in the system. There are three types of users mainly Student, Administrator and Company. The Administrator is the master user; he gets the most number of priorities than the other users. The Companies will have to get register for the first time so that their contact information, papers, vacancies will be provided. Companies can view all students that have applied for vacancies, together with information on their availability, application time, cover letters, attached CVs etc. First the system is test properly and at the same time, the users are trained in the new procedure. Proper implementation is essential to provide a reliable system to meet organization requirement. Implementation includes all those activities that take place to convert from old systems to new.